Erotic Abuse on Woman’s Body: A Study on Chapali Height - Dhakal, Suresh Raj (Kalika Journal of Multidisciplinary Studies, 2022)
The issue of the exploitation of female characters by male ones is a popular subject of filmy contents in different movies.In this regard, the paper examines the film Chapali Height in terms of how an innocent girl is sexually reified by two playboys and how she avenges after realizing the treachery. Bini, a young girl, spiritually and physically loves a boy named Amir and elopes with him, leaving her family behind, but Amir abandons her after sucking the sap of her romantic youth. After that, another mischievous boy, Raj creates a drama of love and exploits her sexually. However, the boys, who are the best friend from the past, already have consensus to romance on her body. The internalization of physical exploitation on her body crosses the limit of her aggression which leads the catastrophic end in the movie. In the study, the entire movie is selected as the text for general discussion where the data will be primarily taken from the erotic snapshots of the movie and the persuading dialogues there. Objectification theory of Fredrickson and Roberts (1997) in relation to body politics is taken as the theoretical base. Besides, this study espouses a qualitative descriptive approach to dig out commodification on woman’s body by man. The finding of this study shows that the extreme physical exploitation to the female ultimately leads the disastrous result. At the end, the commodified woman kills the men by burying them into the ditch.